Reducing and oxidizing agents sensitize heat-activated vanilloid receptor (TRPV1) current - Susankova, Klara; Tousova, Karolina; Vyklicky, Ladislav; Teisinger, Jan; Vlachova, Viktorie (Molecular pharmacology, 2006)
We have previously reported that the reducing agent dithiothreitol (DTT) strongly increases thermally induced activity of the transient receptor potential vanilloid receptor-1 (TRPV1) channel. Here, we show that exposure to oxidizing agents also enhances the heat-induced activation of TRPV1. The actions of sulfhydryl modifiers on heat-evoked whole-cell membrane currents were examined in TRPV1-transfected human embryonic kidney 293T cells. The sensitizing effects of the membrane-permeable oxidizing agents diamide (1 mM), chloramine-T (1 mM), and the copper-o-complex (100:400 microM) were not reversed by washout, consistent with the stable nature of covalently modified sulfhydryl groups. In contrast, the membrane-impermeable cysteine-specific oxidant 5,5'-dithio-bis-(2-nitrobenzoic acid) (0.5 mM) was ineffective. The alkylating agent N-ethylmaleimide (1 mM) strongly and irreversibly affected heat-evoked responses in a manner that depended on DTT pretreatment. Extracellular application of the membrane-impermeable reducing agent glutathione (10 mM) mimicked the effects of 10 mM DTT in potentiating the heat-induced and voltage-induced membrane currents. Using site-directed mutagenesis, we identified Cys621 as the residue responsible for the extracellular modulation of TRPV1 by reducing agents. These data suggest that the vanilloid receptor is targeted by redox-active substances that directly modulate channel activity at sites located extracellularly as well as within the cytoplasmic domains. The results obtained demonstrate that an optimal redox state is crucial for the proper functioning of the TRPV1 channel and both its reduced and oxidized states can result in an increase in responsiveness to thermal stimuli.
Keywords: Mutant Proteins; redukční činidla; peroxid vodíku; Hot Temperature; Oxidants; Mutation, Missense; Dose-Response Relationship, Drug; dithiothreitol; Animals; Mutation; Capsaicin; Hydrogen Peroxide; Sulfhydryl Reagents; vztah mezi dávkou a účinkem léčiva; Humans; Patch-Clamp Techniques; TRPV Cation Channels; sulfhydrylová reagencia; Dithionitrobenzoic Acid; krysa rodu Rattus; kyselina dithionitrobenzoová; membránové potenciály; Rats; Reducing Agents; oxidancia; mutantní proteiny; Cell Line; Diamide; metoda terčíkového zámku; diamid; zvířata; kapsaicin; vysoká teplota; Membrane Potentials; Ethylmaleimide; Transfection; kationtové kanály TRPV; transfekce; mutace; lidé; buněčné linie; missense mutace; ethylmaleimid; Dithiothreitol